The yogasutra of Patanjali a new introduction to the Buddhist roots of the yoga system - Gokhale, Pradīpa, 1953- (Routledge India, 2020)
This book offers a systematic and radical introduction to the Buddhist roots of Ptajala-yoga, or the Yoga system of Patajali. By examining each of 195 aphorisms (stras) of theYogastra anddiscussingtheYogabhya, it shows that traditional and popular views on Ptajala-yoga obscure its true nature. The book argues that Patajali's Yoga contains elements rooted in both orthodoxandheterodox philosophical traditions, including Skhya, Jaina and Buddhist thought. With a fresh translation and a detailed commentary ontheYogastra, the author unearthshow several of the terms, concepts and doctrinesin Patajali's Yoga can be traced to Buddhism, particularly the Abhidharma Buddhism of Vasubandhu and the early Yogcra of Asaga.The work presents theYogastraof Patajali as a synthesis of two perspectives: the metaphysical perspective of Skhya and the empirical-psychological perspective of Buddhism.Based on a holistic understanding of Yoga, the study explores key themes of the text, such as meditative absorption, means,supernormal powers, isolation,Buddhist conceptions of meditation and theinterplay between Skhya and Buddhist approaches to suffering and emancipation. It further highlights several new findings and clarifications on textual interpretation and discrepancies. An important intervention in Indian and Buddhist philosophy, this bookopens upa new way of looking at the Yoga of Patajali in the light of Buddhism beyond standard approaches andwill greatly interest scholars and researchers of Buddhist studies, Yoga studies, Indian philosophy, philosophy in general, literature, religion and comparative studies, Indian and South Asian Studies and the history of ideas.